1994
DOI: 10.1093/nar/22.19.3846
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of mutagenesis by O6-methylguanine in the human Ha-ras oncogene inE.coliandin vitro

Abstract: Single residues of O6-methylguanine (O6-meG) were introduced into the first or second position of codon 12 (GGC; positions 12G1 or 12G2, respectively) or the first position of codon 13 (GGT; position 13G1) of the human Ha-ras oncogene in phage M13-based vectors. After transformation of E.coli, higher mutant plaque frequencies (MPF) were observed at 12G1 and 13G1 than at 12G2 if O6-alkylguanine-DNA alkyltransferase (AGT) had been depleted, while similar MPF were observed at all three positions in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Single-adduct studies have demonstrated that O 6 -meG is strongly premutagenic, giving rise to GC→AT transitions by direct miscoding during cell replication (26)(27)(28), a sequence change which has been found to dominate the mutation spectra induced in vitro and in vivo by S N 1 methylating agents (29)(30)(31). In the case of NDMA, sequence analysis of large numbers of mutants derived from mutagenesis in the lacI gene of Escherichia coli has shown that it induces predominantly GC→AT transitions, as well as a small proportion (~10%) of other types of mutations (30,32).…”
Section: Introductionmentioning
confidence: 99%
“…Single-adduct studies have demonstrated that O 6 -meG is strongly premutagenic, giving rise to GC→AT transitions by direct miscoding during cell replication (26)(27)(28), a sequence change which has been found to dominate the mutation spectra induced in vitro and in vivo by S N 1 methylating agents (29)(30)(31). In the case of NDMA, sequence analysis of large numbers of mutants derived from mutagenesis in the lacI gene of Escherichia coli has shown that it induces predominantly GC→AT transitions, as well as a small proportion (~10%) of other types of mutations (30,32).…”
Section: Introductionmentioning
confidence: 99%
“…In peripheral leukocytes from healthy volunteers the median adduct concentrations were about an order of magnitude lower (range, 0.07-0.46 pmol/μmol Gua) than in liver [121,122] or colon [123]. Nevertheless, this adduct was found in 83-86% in samples of maternal and cord blood leukocyte DNA from healthy smoking and non-smoking women at levels up to 0.2 pmol/μmol guanine [124]. Interestingly, smoking status had no effect on the detected adduct levels.…”
Section: Methylationsmentioning
confidence: 83%
“…With respect to methylations, the highest yields of adducts in the target organs, such as lung, liver and nasal mucosa of rats exposed to NNK have been found for 7-methylguanine (7-mGua), followed by O 6 -methylguanine (O6-mGua), whereas very low levels of O 4 -methylthymidine (O4-mThd) were present [81]. O6-mGua Brought to you by | University of St Andrews Scotland Authenticated Download Date | 6/7/15 5:50 AM is, on the other hand, a highly pro-mutagenic adduct that gives rise to GC to AT transitions [82][83][84] of a type found in codon 12 of the Ki-ras oncogene from mouse lung tumors induced by NNK [85,86]. Some adducts from pyridyloxobutylations (HPB) have recently been identified, and include the HPB 7-and O 6 -guanines, as well as HPB O 2 -cytidine adducts [87].…”
Section: Type Of Dna Adducts From Tobacco Specific Nitrosaminesmentioning
confidence: 99%
“…Another adduct generated by NDMA exposure is O 6 -methylguanine (O6-meG). This adduct is repaired by the protein O 6 -methylguanineDNA methyltransferase, and if not repaired, can produce G:C → A:T transitions (Mirsalis, Mon-forte, and Winegar 1994; Pegg 1990; Pletsa et al 1994; Rossi et al 1989; Tan, Swann, and Chance 1994). The G:C → A:T transition has been associated with an increased risk of cancer (Bedell et al 1982; Swenberg et al 1982).…”
Section: Discussionmentioning
confidence: 99%